Which is the Digital Competence of Each Member of Educational Community to Use the Computer? Which Predictors Have a Greater Infuence? - Guillén-Gámez, Francisco David; Colomo-Magaña, Ernesto; Cívico-Ariza, Andrea; Linde-Valenzuela, Teresa Loreto (Springer, 2023)
Since the COVID-19 pandemic, the use of digital resources and virtual platforms is even more essential to continue the educational process, either in person or online, affecting all the members involved in the teaching–learning process of the students. Therefore, this study is aimed: (1) to know and compare the digital competence of the agents that are the main integrators of the educational community (parents, teachers, students) about the use of the computers, according to gender and educational stage (Pre-school, Primary and Secondary Education stages); and (2) to identify significant predictors that affect the acquisition of this competence. An ex-post-facto design was used with a sample of 786 participants from Andalusia (Spain). Research methods such as contrasts of means and multiple linear regression analysis were used. The results showed high average levels of basic digital competences for all the agents involved. A gender gap was found between mothers and fathers of students, with higher scores for the latter group. In addition, the use of videogames, the parents' academic background and the use of digital tablets or Google+ are the most significant predictors that affect the acquisition of this competence.
Keywords: Enseñanza asistida por ordenador-Evaluación; Digital competence; ICT; Technology; Computers; Educational community